KARAKTERISTIK FISIK MATAAIR PANAS DAERAH SAMBOJA, KUTAI KARTANEGARA - Jamaluddin Jamaluddin; Iwan Prabowo; Maria Maria (PETROGAS: Journal of Energy and Technology, 2021)
Geothermal features can be observed in areas of active volcanism, or areas that have inactive volcanoes. In non-volcanic areas, the temperature of rocks within the Earth also increases with depth. This temperature increase is known as the Geothermal Gradient. If water percolates deeply enough into the crust, it comes into contact with hot rocks and can circulate to the surface to form hot springs. The collection of field hydrothermal data during field study with the help of portable instruments. The different physical parameters of the thermal springs such as temperature, pH, colour, and odour of thermal fluid are noted. The temperature of the thermal springs ranges from 43oC to 48oC. The pH value of the thermal waters shows a neutral (pH 6-6.6) and sulphur odour is discernible particularly. Based on geological, the system geothermal energy that develops is geopressured.